Educación e interculturalidad en el Perú contemporáneo - Caviglia Marconi, Alessandro (2013)
In the following article, the author deepens in the necessity, always presentand always relegated, of the education in our country; that is requiredtaking as a starting point with the purpose to grow in quality levels, principlethat the Peru is from intercultural and multilingual nature, aspects that,according to the author point of view, not always are considered in themoment of making teaching in classroom.